2023
DOI: 10.3390/en16020638
|View full text |Cite
|
Sign up to set email alerts
|

High-Order Compensation Topology Integration for High-Tolerant Wireless Power Transfer

Abstract: Wireless power transfer (WPT) has been a promising way to transfer power wirelessly over certain distances through the mutual inductance (MI) of the magnetically coupled transmitter and receiver coils, providing significant benefits of convenience, safety, and feasibility to special occasions. The stable output and efficiency cannot be maintained due to the load variation and the inevitable misalignment between the magnetic couplers. High-order compensation topologies that are highly flexible in design due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 149 publications
0
3
0
Order By: Relevance
“…The determination of inrush and internal fault currents in transformers is an important feature of the transformer protection scheme proposed in [ 15 , 16 , 17 ]. In particular, in [ 15 ], a classification, in the sense of a discrimination, of internal fault currents and the phenomenon of inrush currents in a transformer is realized by using an EKF algorithm based on the monitoring of current and resistance variation on the primary winding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of inrush and internal fault currents in transformers is an important feature of the transformer protection scheme proposed in [ 15 , 16 , 17 ]. In particular, in [ 15 ], a classification, in the sense of a discrimination, of internal fault currents and the phenomenon of inrush currents in a transformer is realized by using an EKF algorithm based on the monitoring of current and resistance variation on the primary winding.…”
Section: Introductionmentioning
confidence: 99%
“…In [ 16 ], a fault diagnosis in a permanent magnet synchronous generator (PMSG) is proposed and, when the fault appears, an EKF and unscented Kalman filter (UKF) are used to detect the percentage and the place of the fault. In [ 17 ], high-order compensation topology integration for high-tolerant wireless power transfer is proposed, in which description and comparison of highly flexible compensation topologies, including integration methods and relative control strategies for high misalignment-tolerant wireless power transformer systems, are proposed. All of these contributions indicate the importance of the topic as well as the variety of the possible problems that can occur and their possible solutions.…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings from [15], [16] literatures, highly flexible compensation topologies, integration methods, and relative control strategies for high misalignment-tolerant WPT system were discussed. Rehman et al demonstrated, power is conveyed using a magnetic resonance technology with a maximum efficacy of 96% at a distance of 60 cm between the two coils.…”
mentioning
confidence: 99%